Spatial Segregation in Indian Cities: Does the City Size Matter?. (March 2018) - Haque, Ismail; Das, Dipendra Nath; Patel, Priyank Pravin
As India transforms into an increasingly urban society, ward-level data from the 2011 Indian Census is analysed to decipher how inequality patterns vary across different scales of urban settlements, highlighting the spatial segregation by gender, caste, socio-economic status (SES) and access to goods, by examining a specific state (Uttar Pradesh) as a microcosm to account for the nation's enormous socio-political diversity. Caste-based spatial segregation is greater in small and medium cities compared to metropolises, possibly from greater intermingling of socio-cultural identities in larger urban locales that lower caste barriers. This also applies to segregation by SES. Contrastingly, segregation by gender or by access to essential goods is higher in larger and medium cities. Within cities, caste-based segregation is greater than that by SES. A stark spatial segregation in terms of households' (HHs) access to essential public and private goods exists, often higher than even caste-based segregation. Summary explanations for these differentials in spatial segregation across settlements scales are offered, highlighting probable further research aspects.